B- and plasma cell-targeting therapies for podocytopathies: state of the art and the New Gaslini Protocol - Paolo Cravedi; Agnese Spennacchio; Carolina Bigatti; Xhuliana Kajana; Gianluca Caridi; Andrea Angeletti (Clinical Kidney Journal, 2026)
Abstract Podocytopathies, including minimal change disease (MCD), focal segmental glomerulosclerosis (FSGS), and idiopathic nephrotic syndrome (INS), are traditionally classified by histology and corticosteroid responsiveness, but this framework does not capture their biological heterogeneity or underlying mechanisms. Over the past decade, the paradigm of podocyte injury has shifted from a T cell–centric model to a broader immunological framework in which B cells, plasma cells, and humoral immunity play a central role. The identification of circulating autoantibodies, including anti-nephrin antibodies, together with evidence of extrafollicular B-cell activation, supports a model in which humoral immune factors drive podocyte injury. Anti-CD20 therapies have improved outcomes in steroid-dependent and frequently relapsing disease, but their efficacy remains limited in steroid-resistant forms and post-transplant recurrence. This likely reflects incomplete depletion of tissue-resident B cells and persistence of long-lived plasma cells, supporting the need for strategies targeting multiple levels of the humoral immune axis. Recent studies suggest that combined targeting of CD20⁺ B cells and CD38⁺ plasma cells with monoclonal antibodies such as obinutuzumab and daratumumab may achieve deeper and more sustained disease control, including in refractory and recurrent cases. However, variability in treatment approaches across centers underscores the need for standardization. In this review, we summarize evidence supporting the role of humoral immunity in podocytopathies and discuss the strengths and limitations of B cell–directed therapies. We then propose a mechanistically-driven strategy, the New Gaslini protocol, integrating sequential CD20 and CD38 targeting to provide a unified framework for managing severe and relapsing disease.